Impact of temperature on the temporal dynamics of microcystin in Microcystis aeruginosa PCC7806 - Roy, Souvik; Guljamow, Arthur; Dittmann, Elke (Frontiers in Microbiology, 2023)
Cyanobacterial blooms pose a serious threat to water quality and human health due to the production of the potent hepatotoxin microcystin. In microcystin-producing strains of the widespread genus Microcystis, the toxin is largely constitutively produced, but there are fluctuations between the cellular and extracellular pool and between free microcystin and protein-bound microcystin. Here we addressed the question of how different temperatures affect the growth and temporal dynamics of secondary metabolite production in the strain M. aeruginosa PCC 7806 and its microcystin-deficient mcyB mutant. While the wild-type strain showed pronounced growth advantages at 20, 30 and 35°C, respectively, the mcyB mutant was superior at 25°C. We further show that short-term incubations at 25-35°C result in lower amounts of freely soluble microcystin than incubations at 20°C and that microcystin congener ratios differ at the different temperatures. Subsequent assessment of the protein-bound microcystin pool by dot blot analysis and subcellular localization of microcystin using immunofluorescence microscopy showed re-localization of microcystin into the protein-bound pool combined with an enhanced condensation at the cytoplasmic membrane at temperatures above 25°C. This temperature threshold also applies to the condensate formation of the carbon-fixing enzyme RubisCO thereby likely contributing to reciprocal growth advantages of wild type and mcyB mutant at 20 and 25°C. We discuss these findings in the context of the environmental success of Microcystis at higher temperatures.